Socioeconomic and Ethnobotanical Importance of the Breadfruit Tree (Artocarpus Communis J. G & G. Forster) in Benin - Asaël J. Dossa; Juste M. Amanoudo; Towanou Houetchegnon; Christine Ouinsavi (European Scientific Journal, ESJ, 2018)
This study aims to evaluate ethnobotanical knowledge that populations hold and income from the exploitation of the breadfruit (Artocarpus communis) in southern Benin. The data collected by interview and focus group are related to the uses of Artocarpus communis, harvest methods and the habitat of specie. The results show that A. communis is used for: food, trade, artisanal, energetic, cultural and medicinal. Local populations know the species with unequal distribution among gender (Men ID = 0.75 and IE = 0.08) and Women (ID = 0.48 and IE = 0.06); and when it comes to age (Young ID = 0.56 and IE = 0.07; Adult ID = 0.606 and IE = 0.08; Old ID = 0.75 and IE = 0.1) suggesting that people make various uses of the species. The most used plant part was the fruit (VUT=11, 87). These organs (Fruits, Flowers, Leaf), are collected either by picking or collecting, (bark) by debarking and (root) by digging. 50.51% of people surveyed collected those organs on breadfruit trees present at homes, 14.65% on those present in fields, 11.62% in the dregs and 23.23% in fallow lands. The average fruit yield of an orchard is estimated at 17 tonnes/ha, which represents an average income of about 2817 USD/individual/year.